Applying activity-based costing to determine the final costs of radiology services in Shiraz, Iran: a concurrent equations approach - Hossein Khoshnoud Khankahdani (Gonabad University of Medical Sciences, 2019)
The Activity-Based Costing (ABC) method possesses the capability to identify the costs accurately and provide non-financial information for improving system function and increasing its efficiency. The present study aimed to calculate the final costs of radiology services to determine the final costs deviation from the enacted tariffs. This study was a retrospective cross-sectional analysis of radiology final costs for 19 different types of radiology services (1077 stereotypes) at the hospital in Shiraz, Iran. The required data was collected through reports, specified forms, interviewing with hospital personnel and authorities as well as direct observation of hospital activity centers. The final costs of the radiology services were determined using the activity-based costing method as well as the cost sharing of activity centers through concurrent equations technique. The results showed a great amount of loss for all provided services in this center. The Mean tariff of the services equaled 625,626 Rials while the mean final cost of the provided services equaled 3,036,390 Rials. So, the findings of this study show an average loss of 2,410,764 Rials for each service.